The effect of naringenin on oxidative stress in some tissues (heart, lung, brain, spleen, muscle) of lead-treated rats - Eri?Şi?r, Mine; Benzer, Fulya; Özkaya, Ahmet; Dag, Üzeyir (Ataturk Universitesi, 2018)
Naringenin, a flavonoid increases resistance against oxidative stress. The present study aims to investigate the effect of lead on lipid peroxidasyonu and some antioxidants in heart, lung, brain, spleen, muscle and the effect of naringenin on these parameters. Naringenin was administered by orogastric gavage (50 mg/kg, dissolved in corn oil) and lead acetate was given as daily 500 parts per million in drinking water for 4 weeks. In the rats exposed to lead, MDA levels in the brain, lungs, spleen and muscle tissues significantly increased (P<0.001), in the heart tended to increase but not significantly (P>0.05). Lead caused a statistically significant decrease in GSH-Px activity of the brain, spleen and muscle tissues, in CAT activity of the heart, lung and muscle tissues, in GSH concentration of the lungs and muscle tissues (P<0.05). The administration of alone naringenin caused a statistically significant decrease in MDA levels in the heart and muscle, but a significant increase in the lung (P<0.05). Although increased MDA levels in the heart, lungs, brain, muscle and spleen tissues were significantly decreased by use of the naringenin together with lead (P<0.05), increased MDA levels in the lungs and spleen tissues could not be recovered to the normal level. Generally the decreased GSH-Px and CAT activities in these tissues due to lead were significanly increased by naringenin supplementation (P<0.05). In addition, the reduced GSH levels in lung and muscle, the inceased GSH levels in heart with effect of lead were returned to the normal by naringenin. Lead particularly causes to an increase in lipid peroxidation by consuming antioxidants of cells. Naringenin was able to prevent as tissue-specific (brain, muscle) the oxidative stress caused by lead. © 2016 Ataturk Universitesi. All rights reserved.
Kurşun uygulanan ratların bazı dokularında (kalp, akciğer, beyin, dalak, kas) oksidatif stress Üzerine naringeninin etkisi
Keywords: Lead; Naringenin; Oxidative stress